Formas de militância feminista em cenário de auto-organização e ciberativismo no Brasil contemporâneo : tendências atuais a partir do caso de Aracaju/SE - Souza, Maria Erica Santana de (2017)
This dissertation’s main purpose is to discuss forms of militancy in a scenario characterized by the increase in the use of the social networking websites for militant purposes and by the auto-organization as general tendencies since the June 2013 protests, focusing on the feminist struggle in Aracaju. As a more specific issue, it aimed to apprehend the rules and principles, framings, organizational forms and profiles of feminist militancy constituted in this scenario, as well as means and tools used to include their demands in the public arenas of confrontation. From the analytical point of view, the study was based on the assumption that, in order to give intelligibility to the feminist militancy, it was necessary to resort to the gender relations analyses (and its intersections with race, class and sexuality) and to feminist theories, in addition to the general concepts of the sociology of social movements used in this work, given that the women depiction in the public range and the roles historically attributed to them are conceived here as important factors that help us understand the political participation and the organizational forms and tools mobilized in this type of militancy. Assuming a critical perspective that aims to comprehend the logic of formal and informal exclusions of the subordinate groups like women in the public scope demands, conversely, an approach on the points of view of the agents studied about the public, the political participation and the organizational forms presented as an alternative to those institutionalized, as a way of resisting. Therefore, this dissertation’s epistemic-methodological background relied on some tenets of the Latournian sociology in what concerns group formation and also on a feminist epistemology, especially Donna Haraway’s approach, in order to apprehend the feminist movements’ and engagements’ own logics and dynamics from the fieldwork. The research evinced, in general, that the depictions related to the women generated by the gender subordination are expressed in a number of ways as constraints to the feminists’ political participation, however, from another perspective, the emotions that are incongruent with the standard depictions about “being woman” (which varies according to race, class, sexuality, gender identity, among others), converted into moral emotions and a sense of injustice, have played a crucial role to understand the motivations to the individual engagement, the constitution of new collective identities of the movement, and the creation of their own organizational forms. In other words, women’s auto-organization and their autonomous means of publicizing their demands, through the Marchs, the social networking websites, and art in general, are alternatives developed through a feminist vocabulary, constituted from the verification of women’s subordination in the gender relations and the misery experienced in an everyday basis, so that their demands, regarded as merely “private” issues or “secondary” questions, are included in the public arenas and widely debated by society.